2017
DOI: 10.1101/cshperspect.a029793
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle as an Endocrine Organ: The Role of Myokines in Exercise Adaptations

Abstract: Exercise stimulates the release of proteins with autocrine, paracrine, or endocrine functions produced in skeletal muscle, termed myokines. Based on the current state of knowledge, the major physiological function of myokines is to protect the functionality and to enhance the exercise capacity of skeletal muscle. Myokines control adaptive processes in skeletal muscle by acting as paracrine regulators of fuel oxidation, hypertrophy, angiogenesis, inflammatory processes, and regulation of the extracellular matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(222 citation statements)
references
References 233 publications
(198 reference statements)
1
179
0
12
Order By: Relevance
“…Myokines are active substances that are synthesized in the skeletal muscle and regulate the function of tissues such as fat, liver, pancreas, bone, brain, and muscle using autocrine, paracrine, or endocrine mechanisms [15]. Exercise can stimulate the secretion of myokines that protect functionality and enhance the exercise capacity of the skeletal muscle [40]. Myokines act as paracrine regulators of energy oxidation, hypertrophy, angiogenesis, inflammatory processes, and regulation of the extracellular matrix as well as regulate adaptive processes of the skeletal muscle [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myokines are active substances that are synthesized in the skeletal muscle and regulate the function of tissues such as fat, liver, pancreas, bone, brain, and muscle using autocrine, paracrine, or endocrine mechanisms [15]. Exercise can stimulate the secretion of myokines that protect functionality and enhance the exercise capacity of the skeletal muscle [40]. Myokines act as paracrine regulators of energy oxidation, hypertrophy, angiogenesis, inflammatory processes, and regulation of the extracellular matrix as well as regulate adaptive processes of the skeletal muscle [40].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise can stimulate the secretion of myokines that protect functionality and enhance the exercise capacity of the skeletal muscle [40]. Myokines act as paracrine regulators of energy oxidation, hypertrophy, angiogenesis, inflammatory processes, and regulation of the extracellular matrix as well as regulate adaptive processes of the skeletal muscle [40]. They also have reported endocrine functions in body weight regulation, low-grade inflammation, insulin sensitivity, suppression of tumor growth, and improvement of cognitive function [40].…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is able to communicate with other organs via secretory peptides, the so-called myokines [22][23][24][25][26]. The muscle secretome consists of several hundred secreted peptides, which provides a conceptual basis for understanding how muscles communicate with other organs.…”
Section: Anti-inflammatory Effects Of Acute Exercisementioning
confidence: 99%
“…Recent analyses of muscle secretomes revealed that aerobic exercise or strength training trigger the secretion of numerous myokines [11]. Importantly, it is worth noting that the production of "positive" myokines is as much promoted by physical exercise as it is repressed by physical inactivity, highlighting the importance of lifestyle for healthspan [112]. More precisely, during exercise skeletal muscle tightly interacts with adipose tissue, pancreas, and liver to sustain the energy demands of physical activity and mediate positive effects in wholebody energy metabolism.…”
Section: Inter-organ Communication During Exercisementioning
confidence: 99%